MEWUJUDKAN ASPEK KEADILAN DALAM PUTUSAN HAKIM DI PERADILAN PERDATA - Djojorahardjo, Rommy Haryono (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
The judge's decision in court ideally contains aspects of legal certainty, justice and expediency. In its implementation it is not easy to synergize these three aspects, especially between aspects of legal certainty and justice, which are usually conflicting. The results showed that a judge in examining and deciding cases was not always fixed on just one principle. Constraints faced by judges who tend to legal certainty experience a deadlock when written provisions cannot answer the existing problems. Emphasis that is more inclined to the principle of justice means having to consider the law that lives in the community, which consists of habits and legal provisions that are not written. Judges in their legal reasons and considerations must be able to accommodate all the provisions that live in society in the form of customs and unwritten legal provisions. The emphasis is more on the principle of expediency, more nuanced in the economy